Anatomia de uma empresa militar e de segurança privada: a empresa DynCorp em perspectiva global - Paoliello, Tomaz [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Private military and security companies (PMSC) is a new actor that has attracted great attention in the debates within the International Relations discipline. Through the study of a particular north-american company, DynCorp, we seek to investigate the nature of these actors in the great process of globalization. The literature on PMSC usually presents the idea that the emergence of such players has occurred through spontaneous supply and demand forces. The hypothesis that assist this idea is that the states are moving away from the new wars. Here this hypothesis is challenged and replaced by another. The State, particularly the US, has adapted its engagement in capacity in conflicts by engaging the PMSC, and stimulating the growth of a private security market. DynCorp is part of this movement. We investigate the relationship of co-constitution, in which companies and state are organized to develop the new "market for force", and the birth of PMSC as actors of a hybrid nature, associated with the transformation of the neoliberal state. The study of DynCorp unfolds in three dimensions: its corporate face, as a transnational company associated with market principles; a fighting face, as one of the new actors on the stage of contemporary conflicts; and as a constituent part of a foreign policy apparatus, associated with their only customer, the United States government.

As empresas militares e de segurança privada (PMSC) são um novo ator que tem despertado grande atenção nos debates dentro da disciplina Relações Internacionais. Através do estudo de uma companhia especificamente, a norteamericana DynCorp, procuramos investigar qual a natureza desse ator dentro do grande processo de globalização. A literatura sobre as PMSC geralmente apresenta a ideia de que o aparecimento de tais atores tenha ocorrido através de forças de oferta e demanda espontâneas e circunstanciais. A hipótese auxiliar dessa ideia, que os Estados estejam se afastando das novas guerras, é aqui desafiada e substituída por outra. O Estado, particularmente os EUA, se adaptou em sua capacidade de engajamento em conflitos através da contratação das PMSC, e estimulou o crescimento de um mercado de segurança privada. A empresa Dyncorp faz parte desse movimento. Investigaremos a relação de co-constituição, na qual empresas e Estado se articulam para desenvolver o novo “mercado da força”, e o nascimento das PMSC como atores de natureza híbrida, associados às transformações do Estado neoliberal. O estudo da DynCorp se desdobra em três dimensões: sua face empresarial, como companhia transnacional associada às lógicas de mercado; uma face combatente, um dos novos atores nos palcos de conflitos contemporâneos; e como parte constituinte de um aparato de política externa, associado a seu cliente único, o governo dos Estados Unidos.
The anatomy of a private military and security company: DynCorp through a global perspective
Keywords: PMSC; DynCorp; Estados Unidos; Empresas militares e de segurança privada; Segurança privada; Terceirização; Private military and security companies; Private security; Outsourcing; United States